Harnessing myeloid cells in cancer - Su-Yeon Park; Ekaterina Pylaeva; Vikas Bhuria; Adriana Rosa Gambardella; Giovanna Schiavoni; Dimitrios Mougiakakos; Sung-Hoon Kim; Jadwiga Jablonska (Molecular Cancer)
Abstract Cancer-associated myeloid cells due to their plasticity play dual roles in both promoting and inhibiting tumor progression. Myeloid cells with immunosuppressive properties play a critical role in anti-cancer immune regulation. Cells of different origin, such as tumor associated macrophages (TAMs), tumor associated neutrophils (TANs), myeloid derived suppressor cells (also called MDSCs) and eosinophils are often expanded in cancer patients and significantly influence their survival, but also the outcome of anti-cancer therapies. For this reason, the variety of preclinical and clinical studies to modulate the activity of these cells have been conducted, however without successful outcome to date. In this review, pro-tumor activity of myeloid cells, myeloid cell-specific therapeutic targets, in vivo studies on myeloid cell re-polarization and the impact of myeloid cells on immunotherapies/genetic engineering are addressed. This paper also summarizes ongoing clinical trials and the concept of chimeric antigen receptor macrophage (CAR-M) therapies, and suggests future research perspectives, offering new opportunities in the development of novel clinical treatment strategies.